Obrót cywilnoprawny nieruchomościami w ramach kooperatyw mieszkaniowych - Wojdył, Sebastian (PRAWO i WIĘŹ, 2024)
The paper discusses the peculiarities of real estate transactions regarding the functioning of civil law transactions of the new institution of housing cooperatives. As part of the inspiration of the regulation, attention was paid to the historical reference to analogous solutions functioning both abroad (especially in the field of the so-called Antigonish movement) and solutions functioning in Poland (including Kooperatywa Mieszkaniowa Pomorze or Wrocławska Kooperatywa Mieszkaniowa). Because of the signaled problem of naming and its translation into foreign languages, the concept of using the term community housing (co-housing). The divergence of the institution with the solutions operating within the framework of cooperative law was emphasized, where the only link between the two solutions is the possibility of transferring rights and obligations to the newly established housing cooperative.